Pr??ticas adaptativas de gerenciamento de projetos na proposi????o de novos cursos strcito sensu profissionais a dist??ncia - Souza, Luiz Felipe Pinto de (2020)
Project management has been used as a management scheme for educational institutions to obtain results that are in accordance with the institutions' strategy. The offer of stricto sensu postgraduate courses in Brazil is guided by CAPES, both through guidance and with the evaluations carried out by it, both for the entry and for the permanence of courses in the National Postgraduate System (SNPG). However, the direction for offering these distance courses is not yet detailed by CAPES. Furthermore, the CAPES evaluation form is in being updated, which may make it difficult for HEIs to prepare a new course proposal, especially in distance learning. Using Design Science Research, this work aims to propose a method, created from adaptive project management practices, since adaptation allows better management of projects considering their uncertainty. Adaptive project practices are actions, techniques and tools that are used in project management and have also been used by educational institutions. The work was based on the conceptual model generated from a bibliographic review on postgraduate management models, distance education and adaptive design practices. Interviewing specialists, it was understood how the courses are created and their proposals submitted and approved, and the difficulties encountered by these professionals when combining their experience in face-to-face courses with the incipient guidelines for the creation of distance courses were perceived. Based on these elements, the so-called 'Distance MP creation model' was created or manufactured, which has the following elements: (1) stages, in which they are described as sequential activities of the course development project; (2) which adaptive practices can be applied to each activity, be it an action, technique or tool; and (3) an indication of the team responsible and active in each stage.